Determining the correlation between transition zone index with international prostate symptom score and peak flow rate on clinical outcome after transurethral resection of the prostate in benign prostatic hyperplasia - Mohanty, Nalinikanta; Swain, Samir; Hasan, Arshad; Singh, Gyanprakash; Hota, Datteswar (International Surgery Journal, 2019)
Background: Benign prostatic hyperplasia (BPH) is a pathologic process which has common contribution to lower urinary tract symptoms (LUTS) in aging men. International Prostate Symptom Score (IPSS) is an important means of assesment in the clinical research of LUTS and BPH. Free flow rates (peak flow rate or Qmax) give an indirect measure for the probability of obstruction whereas subvesical obstruction only can be measured by invasive pressure-flow studies. Among the various surgical or minimally invasive techniques available for BPH like Intraprostatic stents (temporary/permanent), transurethral needle ablation (TUNA), transurethral microwave thermotherapy (TUMT), transurethral electrovaporization of prostate (TUVP), Transurethral incision of prostate (TUIP), lasers (Nd: YAG (Neodymium-doped yttrium aluminium garnet), Ho: YAG (Holmium yttrium aluminium garnet), potassium titanyl phosphate (KTP), diode, thulium laser) etc, transurethral resection of the prostate (TURP) is a safe and effective procedure. Comparison of difference in the pre and postoperative ultrasonic prostatic volume with amount of tissue resected at operation has established the accuracy of the method. The aims of present study are to determine the correlation between transition zone index with international prostate symptom score (IPSS) and peak flow rate (Qmax) on clinical outcome after TURP in BPH patients. Methods: A prospective study was conducted to determine the effect of the extent of tissue resection on symptom improvement after TURP in men and to evaluate any potential correlation between prostate size and outcome. Results: Total of 52 patients studied prospectively. Transitional zone (TZ) index was found to have a significant correlation with the clinical outcome. Conclusions: Symptomatic improvement after TURP will depend on the amount of tissue resected in terms of IPSS and peak flow rates.